2015
DOI: 10.1186/s12870-015-0612-4
|View full text |Cite
|
Sign up to set email alerts
|

Wheat WCBP1 encodes a putative copper-binding protein involved in stripe rust resistance and inhibition of leaf senescence

Abstract: BackgroundStripe rust, a highly destructive foliar disease of wheat (Triticum aestivum), causes severe losses, which may be accompanied by reduced photosynthetic activity and accelerated leaf senescence.MethodsWe used suppression subtractive hybridization (SSH) to examine the mechanisms of resistance in the resistant wheat line L693 (Reg. No. GP-972, PI 672538), which was derived from a lineage that includes a wide cross between common and Thinopyrum intermedium. Sequencing of an SSH cDNA library identified 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Further analysis of 12 samples showed that the greatest difference in gene expression following F. graminearum infection occurred between different tissues (spike vs. leaf), while the smallest difference was observed between the resistant and susceptible genotypes ( Figure 3 B). This could be due to the fact that L693 and L661 have similar genetic backgrounds [ 16 , 20 , 23 ]. The fact that the greatest difference in gene expression occurred between the spike and leaf indicated that the transcriptome data were reliable to some degree, which could be a real response after F. graminearum infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further analysis of 12 samples showed that the greatest difference in gene expression following F. graminearum infection occurred between different tissues (spike vs. leaf), while the smallest difference was observed between the resistant and susceptible genotypes ( Figure 3 B). This could be due to the fact that L693 and L661 have similar genetic backgrounds [ 16 , 20 , 23 ]. The fact that the greatest difference in gene expression occurred between the spike and leaf indicated that the transcriptome data were reliable to some degree, which could be a real response after F. graminearum infection.…”
Section: Discussionmentioning
confidence: 99%
“…Following pathogen attack, plants must redistribute energy and resources from the primary metabolism to the induced reaction [ 24 ]. Previous studies of wheat spike diseases such as FHB have usually focused on gene expression changes only in local spike tissue, whereas studies of wheat leaf diseases, such as stripe rust and powdery mildew, have focused on gene expression changes only in the local leaf tissue [ 13 , 23 ]. Gene expression changes in distant tissues of plants infected by pathogens, such as the leaves of wheat plants infected by F. graminearum, have not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Many research studies have shown that plant photosynthesis can be greatly reduced when disease symptoms are developing after inoculation with stripe rust [14,18,49,50]. Chlorophyll fluorescence has been shown to be a useful method for the investigation in photosynthesis under different stressful conditions including pathogen infection [51].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Pst infection can change the photosynthetic efficiency of the host wheat. Some studies indicated that the photosynthetic activities were closely correlated with stripe rust, and PSII was easily damaged by Pst infection in wheat [14,18]. Even though in a resistant wheat cultivar, the photosynthetic rate significantly decreased after symptoms appear and signs develop.…”
Section: Introductionmentioning
confidence: 99%
“…YU25 was derived from the cross between common wheat and Thinopyrum intermedium [ 21 , 36 ]. However, genomic in situ hybridization demonstrated that there is no alien chromosome fragment in PI 672538 [ 73 ]. In addition, in the present research, the responses of PI 672538/L1034 and crosses of the F 1 , F 2 , and F 2:3 populations to powdery mildew in different growth phases revealed PI 672538 resistance at both the seedling stage and in adult plants ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 99%